Two Cases of Sternalis Muscle in Humans: Clinical Considerations - Borthakur, Dibakar; Kaushal, Parul; Saravanan, Kamalesh; Jhajhria, Saroj Kaler (Prague medical report, 2025)
The sternalis is an occasional muscle of the pectoral region with a reported incidence of around 7.8%. Higher rates of occurrences have been noted in females and in Asians. The muscle becomes clinically relevant as the muscle can be mis-interpreted as a pathological mass. Routine dissection was performed in a 68-year-old male and a 65-year-old female donated cadavers in the pectoral region. Gross anatomical features were meticulously noted, photographed and measurements were recorded with digital Vernier callipers. In the male cadaver, a long, slender, flat bi-tendinous sternalis was found, and in the female cadaver, tripartite sternalis possessing three distinct bellies was observed. Both the sternalis was right sided and were supplied by 2nd, 3rd and 4th intercostal nerves. Single bellied and tripartite sternalis are rare and they need to be recognized in the diagnostic images and during surgeries to avoid confusion.
Keywords: mrtvola; Cadaver; Female; Aged; Sternalis; Sternalis muscle; Humans; ženské pohlaví; mužské pohlaví; senioři; lidé; Male; prsní svaly; Pectoral region; Pectoralis Muscles